Anti inflammatory Activity of MangiferaIndica Peel - Joel Simon, Christopher; R.V, Geetha; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Mangifera indica (commonly known as mango) is a widely used herb in Ayurvedic medicine. Although numerous review articles on this plant are already published, this review article aims to compile all updated information on its phytochemical and pharmacological activities, assessed through various methods. Studies indicate that mango possesses antidiabetic, antioxidant, antiviral, cardiotonic, hypotensive, and anti-inflammatory properties. Aim: The aim of the study is to investigate the in vitro anti-inflammatory activity of *Mangifera indica* peels.Method: The reaction mixture consisted of the test extract at different concentrations and a 1% aqueous solution of bovine albumin fraction. The pH of the reaction mixture was adjusted using a small amount of 1N HCl. The samples were incubated at 37°C for 20 minutes, then heated at 57°C for an additional 20 minutes. After cooling, the samples' turbidity was measured spectrophotometrically at 660 nm.The experiment was performed in triplicate.Result: Protein denaturation is a well-documented cause of inflammation. In investigating the mechanism of the anti-inflammatory activity, the extract's ability to inhibit protein denaturation was studied.